Pengaruh Model Pembelajaran Learning Cycle 5E terhadap Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas IX SMPN 2 Lubuk Alung - METTIA NORA . (Jurnal Edukasi dan Penelitian Matematika, 2019)
Problem solving ability is one of the goals of mathematical learning that must be owned by student. But learning activities is not optimal in facilitating student to improve problem solving ability, so result of test show that student problem solving ability of SMPN 2 Lubuk Alung is still low. One of effort to overcome this problem is to apply Learning Cycle 5E model. The purpose of  the research is to describe whether problem solving ability of student who learn by using Learning Cycle 5E is more better than student who learn by using conventional learning in class IX SMPN 2 Lubuk Alung. This type of research is quasy experiment  with static group design. The population is all of student in class IX SMPN 2 Lubuk Alung. The sample taking by random sampling, class IX 1 as an experiment class and IX 2 as an control class. The Instrument is used by test of problem solving ability. Based on the result of data analysis, it is got P-value = 0,01 where P-value is less than . It was concluded that problem solving ability of student who learn by using Learning Cycle 5E model is more better than student who learn by using conventional learning in class IX SMPN 2 Lubuk Alung. Keywords – Learning Cycle 5E, Problem Solving Ability